Calcium Allocation to the Tree Canopy and the Edible Part of Sweet Cherry Fruit Is Hindered by Boron Soil Deficiency - Claudia Bonomelli; Gerardo Arredondo; Adriana Nario; Pamela Artacho; Carolina Contreras (Agronomy)
Calcium (Ca) and Boron (B) are structural components of the cell wall with limited phloem mobility. The absorption, movement, and distribution of these two nutrients have a greater effect on leaves than on fruits since their transport is dependent on transpiration flow. This research aimed to study the absorption and movement of 45Ca applied to the soil and the fruit of sweet cherry trees under B-deficient and B-adequate soil conditions. In the first experiment, 45Ca was applied to the soil surface before the occurrence of leaf senescence. Soil and tree components were sampled and analyzed 6 months after 45Ca application. The second experiment involved a 45Ca application to the surface of small fruits with 5 mm diameters, which were analyzed after 45 days. The tree Ca allocation in the B-deficient soil condition was significantly fewer in shoots and higher in roots, contrary to the B-adequate soil. On the other hand, the fruit evidenced significant differences in Ca levels in the edible portion of the fruit (i.e., the flesh and peel), which was higher in the B-adequate soil condition. Therefore, under B-deficient soil, Ca was ‘retained’ in the root system and in the fruit pit, suggesting a synergistic mechanism between Ca and B. This mechanism might indicate a survival ecological function where B triggers biological signals to restore Ca homeostasis.